Visualization of Vaccine Dynamics with Quantum Dots for Immunotherapy. (5th October 2021) - Sun, Junlin; Liu, Feng; Yu, Wenqian; Fu, Dandan; Jiang, Qunying; Mo, Fengye; Wang, Xiuyuan; Shi, Tianhui; Wang, Fuan; Pang, Dai‐Wen; Liu, Xiaoqing
Abstract: The direct visualization of vaccine fate is important to investigate its immunoactivation process to elucidate the detailed molecular reaction process at single‐molecular level. Yet, visualization of the spatiotemporal trafficking of vaccines remains poorly explored. Here, we show that quantum dot (QD) nanomaterials allow for monitoring vaccine dynamics and for amplified immune response. Synthetic QDs enable efficient conjugation of antigen and adjuvants to target tissues and cells, and non‐invasive imaging the trafficking dynamics to lymph nodes and cellular compartments. The nanoparticle vaccine elicits potent immune responses and anti‐tumor efficacy alone or in combination with programmed cell death protein 1 blockade. The synthetic QDs showed high fluorescence quantum yield and superior photostability, and the reliable and long‐term spatiotemporal tracking of vaccine dynamics was realized for the first time by using the synthetic QDs, providing a powerful strategy for studying immune response and evaluating vaccine efficacy. Abstract : Visualization of spatiotemporal trafficking of vaccines is achieved with synthetic QDs for potent immune activation.